The THE EFFECT OF CUSTOMER SATISFACTION ON THE DESIRE TO SWITCH ONLINE SHOPPING EXPERIENCE FROM SOCIAL COMMERCE (INSTAGRAM) TO E-COMMERCE (SHOPEE) - Nursabrina, Alya Rahma; Tania, Lusi (Kinerja, 2024)
Consumer behavior has changed significantly as a result of the growth of social commerce and e-commerce platforms. More and more people are now opting for an online shopping experience that meets their various needs. The study looked at the relationship between consumer satisfaction and the likelihood of moving from Instagram-based social commerce to Shopee-based e-commerce. Specifically, he looked at how users' happiness with Instagram's social commerce capabilities affected their desire to move to Shopee's online store. Using a mixed approach, the study included quantitative information. The number of samples in this study was 265 respondents and data processing using SmartPLS. These findings suggest that the likelihood of consumers migrating to Shopee is significantly positively influenced by their happiness with Instagram's social commerce capabilities. In addition, the study found that important variables influencing the decision to switch were perceived value, reliability, and simplicity of using Instagram's social commerce capabilities. The study's findings have a significant impact on companies operating in the social and e-commerce sectors. This emphasizes how important it is to place customer satisfaction and design a smooth cross-platform buying experience to win new customers.